Simulação e análise econômica da produção in vivo e in vitro de embriões em bovinos - Beltrame, Renato Travassos; Quirino, Celia Raquel; Barioni, Luis Gustavo; de Lima, Vera Fernanda Martins Hossepian [UNESP] (FapUNIFESP (SciELO), 2010)
The objective of this work was to evaluate the effect of the variables number of recipients, synchronization protocol, reproductive efficiency indicators and pregnancy cost, in the economic effectiveness of in vivo and in vitro bovine embryo production. A simulation application was elaborated to allow the user to insert the input variable parameters. A basic scenario, from the efficiency traditional rates of in vivo (ET) and in vitro production (IVP) techniques of bovine embryos, was introduced in the software as a criterion to compare the results. This software was able to reproduce both ET and IVP scenarios. The embryo production was simulated through stochastic simulation. The optimal number of recipients using sensitivity analysis was determined. The net present value and cost per pregnancy were used as a decision parameter. The synchronization for fixed-time embryo transfer decreased the recipient idleness and, consequently, the final cost of pregnancy, in comparison to the traditional methodology. Foetal sexing must be associated to IVP of bovine embryos. In addition, the optimal recipient number per donor is variable and depends on data inserted in the system.
Simulation and economic analysis of in vivo and in vitro bovine embryo production
Keywords: Bos taurus; Cattle; Models; Recipients; Reproduction; Viability